APAKAH ATRIBUT PRODUK COFFEE SHOP MAMPU MENDORONG MINAT PEMBELIAN?: STUDI KASUS PADA PEMBELIAN KOPI LOKAL - Eddy Syah Yahya; Arie Indra Gunawan (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2021)
AbstractThe research conducted tries to explore the coffee shop's attributes in influencing the lokal coffee purchase intention. Attributes consist of 5 variable dimensions such as product quality, service quality, brand equity, facilities and atmosphere. The research design used a descriptive design with a questionnaire distributed to 230 respondents to coffee shop customers. Statistical analysis was used to test the variables using multiple linear regression analysis to determine the effect of lokal coffe attributes in coffee shop on purchase intention. The results of this study indicate that the lokal coffe product attributes in coffee shop have a strong advantage in building consumer buying intention. The results of further research show that only three variables in product attributes have a positive influence on consumer purchase intention, there are product quality, service quality, and facilities. The research finding is that the purchase intention of local coffee products is indeed less when compared to imported coffee products. Customers tend to be low in stating that they will buy local coffee products, and respondents are less interested in searching for information on local coffee in coffee shops. However, the product attributes associated with local coffee served in coffee shops have resulted in a purchase intention of 52.6%.Keywords: Product Attribute, Buying Intention, Coffe shop.